Efficacy of IAA, IBA and magnesium nitrate on summer squash shelf life - AL-Barzinji, Ikbal Muhammed-Gharib (Sulaimani Journal for Pure and Applied Sciences, 2018)
A complete randomized design experiment with ten treatments and three replications was conducted to evaluate the effects of dipping fruits for 5 minutes in one of the following solutions: tap water, 10, 20 and 30 ppm of indoleacetic acid (IAA) or indolebeuteric acid (IBA) or 0.1, 0.2 and 0.3% magnesium nitrate salt (Mg(NO3)2) on the shelf-life characters of summer squash (Cucurbeta pepo L.) fruits, including that harvested incorrectly (without remaining part of the stem) as it proceeds by most Iraqi farmers. The results show a significant decrease in each of peroxidase enzyme activity to 4.94 absorbing unit/minute/ml and weight loss to 9.98% in the fruits that treated with 10 ppm of IAA compared to other treatments. Treating fruits with 20 ppm of IAA increased the fruits peel content of chlorophyll a and chlorophyll b. The fruits total soluble solids increased significantly to 5.33% when they dipped in 20 ppm IBA. There were non-significant differences between the treatments firmness, except the significant decrease to 5.14 kg/cm2 when 0.3% magnesium nitrate was used. Nevertheless, most differences between treatments were non-significant compared to the control fruits. Treating the fruits of summer squash with 10 ppm IAA was the best for decreasing peroxidase activity and fruits weight loss after keeping at ambient temperature (20-23°C and 40-55% relative humidity) for 5 days.
Keywords: Cucurbeta pepo L; IAA; IBA; Magnesium nitrate; Shelf life quality